Riesgos ergonómicos y enfermedades profesionales en el área de producción - conversión de los trabajadores de la empresa Productos Familia Sancela del Ecuador S.A. de la provincia de Cotopaxi. Diseño de una propuesta de intervención. - Niza Aimacaña, Janeth Angela (2014)
FAMILY OF PRODUCTS ECUADSOR Sancela SA It is a company dedicated to the production and commercialization, national and international markets for personal items and general cleaning, it is located in the Parish of Tanicuchi Lasso, Cotopaxi Province, industry processes and jobs involving all types of occupational hazards. For the type of manufacturing activity with the company one of the most outstanding is the ergonomic risks; to control it is desirable from a risk identification and then measure and compare the permissible limits, this assessment will determine the risk exceeds the safety standards set out in the rules and laws and only those that cause health damage workers will be subject to control. This research paper identifies, measures, evaluates and controls the ergonomic risk arising from different jobs, especially where there is repetitive movements that cause the occurrence of occupational diseases; observation, field research, library research, once identified measured and evaluated through OWAS method of analyzing repetitive movements and: to identify the presence of risk research methods such as used negative effects on workers. With the results of the respective study a proposed intervention itself which consists in developing a program and prevention manual is designed skeletal muscle disease, allowing these to improve the health of workers in the area of Business Conversion Sancela Family of Products Ecuador SA. By not taking the company appreciates the importance of ergonomic risk in a future projection will still subjected percentage growth; about diseases that develop from repetitive movements performed in work activities of workers who will be able to prevent them with the training and delivery of manual prevention occupational diseases due to repetitive movements.